ETIKA KEUTAMAAN DALAM AKHLAK TASAWUF ABDUL QODIR AL-JAILANI: RELEVANSINYA DENGAN PENGEMBANGAN KARAKTER MANUSIA - Mustaghfiroh, Siti; Nazar, Taufid Hidayat; Safe'i, Badarudin (JURNAL ISLAM NUSANTARA, 2021)
This study examines the concept of Abdul Qadir al-Jailani's Sufism which is oriented towards moral Sufism. His teachings are centered on improving human morals. Moral perfection in humans can be realized by purification of the soul through the stages of self-purification. This research is a library research, using the formal object of virtue ethics and the material object is the moral thought of Sufism Abdul Qadir al-Jailani. This research is library research. the method used is qualitative with content analysis techniques Interpretation, coherence and holistic. The results of this study indicate that the thought of Abdul Qadir al-Jailani's Sufism emphasizes the aspects of improving individual human behavior through several stages of purification of the soul: repentance, zuhud, tawakal, patience, honesty, gratitude, and pleasure. The ethics of virtue in the Sufism of Abdul Qodir al-Jailani directs the focus of his attention on human being which is oriented to self-improvement as a good or bad person.